The molecular basis of antigenic variation among A(H9N2) avian influenza viruses. Issue 1 (December 2018) - Peacock, Thomas; Harvey, William; Sadeyen, Jean-Remy; Reeve, Richard; Iqbal, Munir
Abstract Avian influenza A(H9N2) viruses are an increasing threat to global poultry production and, through zoonotic infection, to human health where they are considered viruses with pandemic potential. Vaccination of poultry is a key element of disease control in endemic countries, but vaccine effectiveness is persistently challenged by the emergence of antigenic variants. Here we employed a combination of techniques to investigate the genetic basis of H9N2 antigenic variability and evaluate the role of different molecular mechanisms of immune escape. We systematically tested the influence of published H9N2 monoclonal antibody escape mutants on chicken antisera binding, determining that many have no significant effect. Substitutions introducing additional glycosylation sites were a notable exception, though these are relatively rare among circulating viruses. To identify substitutions responsible for antigenic variation in circulating viruses, we performed an integrated meta-analysis of all published H9 haemagglutinin sequences and antigenic data. We validated this statistical analysis experimentally and allocated several new residues to H9N2 antigenic sites, providing molecular markers that will help explain vaccine breakdown in the field and inform vaccine selection decisions. We find evidence for the importance of alternative mechanisms of immune escape, beyond simple modulation of epitope structure, with substitutions increasing glycosylation or receptor-binding avidity, exhibiting the largest impacts on chicken antisera binding. Of these, meta-analysis indicates avidity regulation to be more relevant to the evolution of circulating viruses, suggesting that a specific focus on avidity regulation is required to fully understand the molecular basis of immune escape by influenza, and potentially other viruses.